Differentially expressed genes in giant cell tumor of bone - Babeto, Erica [UNESP]; Giacometti Conceicao, Andre Luis [UNESP]; Valsechi, Marina Curado [UNESP]; Peitl Junior, Paulo [UNESP]; Pires de Campos Zuccari, Debora Aparecida; Cernaglia Aureliano de Lima, Luiz Guilherme; Bonilha, Jane Lopes; Calmon, Marilia de Freitas [UNESP]; Cordeiro, Jose Antonio; Rahal, Paula [UNESP] (Springer, 2011)
Giant cells tumors of bone (GCTB) are benign in nature but cause osteolytic destruction with a number of particular characteristics. These tumors can have uncertain biological behavior often contain a significant proportion of highly multinucleated cells, and may show aggressive behavior. We have studied differential gene expression in GCTB that may give a better understanding of their physiopathology, and might be helpful in prognosis and treatment. Rapid subtractive hybridization (RaSH) was used to identify and measure novel genes that appear to be differentially expressed, including KTN1, NEB, ROCK1, and ZAK using quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry in the samples of GCTBs compared to normal bone tissue. Normal bone was used in the methodology RaSH for comparison with the GCTB in identification of differentially expressed genes. Functional annotation indicated that these genes are involved in cellular processes related to their tumor phenotype. The differential expression of KTN1, ROCK1, and ZAK was independently confirmed by qRT-PCR and immunohistochemistry. The expression of the KTN1 and ROCK1 genes were increased in samples by qRT-PCR and immunohistochemistry, and ZAK had reduced expression. Since ZAK have CpG islands in their promoter region and low expression in tumor tissue, their methylation pattern was analyzed by MSP-PCR. The genes identified KTN1, ROCK1, and ZAK may be responsible for loss of cellular homeostasis in GCTB since they are responsible for various functions related to tumorigenesis such as cell migration, cytoskeletal organization, apoptosis, and cell cycle control and thus may contribute at some stage in the process of formation and development of GCTB.
Keywords: Giant cell tumor of bone; RaSH; Gene expression; Methylation; Quantitative real-time polymerase chain reaction (qRT-PCR); Immunohistochemical